The impact of oestrus synchronization by hormone medication and varying numbers of artificial insemination sessions, determined by sow reproductive indices - Mavromati, Jani (Array, 2021)
This study was conducted on a central Albanian pig farm with a capacity of 80 sows. A uniform distribution of piglets born and the number of reared piglets sold every week and month was the target. To achieve this goal, a hormone-based synchronization scheme was used, combined with the use of one, two, or three artificial insemination sessions during the same oestrus. The main reproduction indices of sows were monitored, and the results indicated that the farrowing rate after the first insemination was 78.57%, 83.64% and 83.33% for the three groups in which one, two and three artificial insemination sessions were used during the same oestrus, obtained by inoculation with the hormone Sergon PG 400/200 IU. Average litter size (the number of live born piglets) per farrowing sow was 10.22 ± 0.33, 10.8 ± 0.2 and 10.6 ± 0.3 in the three groups, respectively. The fecundity index (FI) was 803, 905.8 and 883.3 in the three experimental groups of sows, respectively. A total of 1436 piglets from 136 farrowing sows were sold during 2018, achieving uniform sales of over 100 pigs per month with a weight over 90 kg. Therefore, it can be concluded that oestrus synchronization of sows with the Sergon PG 400/200 hormone can achieve a uniform distribution of piglets born and consequently a uniform distribution of piglets sales per week or month, regardless of the fact that this should be achieved at a larger scale. The best result as seen in the reproductive indicators was achieved by the use of artificial insemination with two sperm inoculations at a 12-hour interval during the same oestrus, synchronized by the Sergon PG 400/200 hormone.